2005
DOI: 10.1055/s-2005-861358
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gastroenteric Anastomosis Using Magnets

Abstract: Our results demonstrate the feasibility, safety. and efficacy of this technique for creating a gastroenteric anastomosis. The success rate was 86.6 %, there were no immediate complications, and there was no mortality related to the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 11 publications
0
39
0
5
Order By: Relevance
“…However one can argue that this method with magnets is also used to perform nonsurgical gut anastomoses [11,12] and there is the risk of inducing ischemia and necrosis in the gullet wall. Apart from the fact that mucosal tissue enclosed between the two magnets does not contain vessels, it is necessary to specify that the attractive force between our magnets was 0.16 N/cm 2 of material, a value markedly lower than that previously used for performing gut anastomoses [11], which was 0.52 N/cm 2 of material.…”
Section: Discussionmentioning
confidence: 99%
“…However one can argue that this method with magnets is also used to perform nonsurgical gut anastomoses [11,12] and there is the risk of inducing ischemia and necrosis in the gullet wall. Apart from the fact that mucosal tissue enclosed between the two magnets does not contain vessels, it is necessary to specify that the attractive force between our magnets was 0.16 N/cm 2 of material, a value markedly lower than that previously used for performing gut anastomoses [11], which was 0.52 N/cm 2 of material.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Swain and Mills reported on gastrojejunostomy performed using flexible forward-view endoscopy using a special compression button [13]. Since then, several investigators reported on gastrojejunostomy using flexible forward-view endoscopy in mainly animal studies and a few clinical studies using flared-type metal stents, magnets or natural orifice transluminal endoscopic surgery [14][15][16][17][18][19][20]. In 2002, Fritscher-Ravens et al reported on EUS-guided gastrojejunostomy in pigs using a special compression button [21,22].…”
Section: Endoscopic Gastrojejunostomymentioning
confidence: 99%
“…Im Anschluss kann in einem zweiten Schritt eine weiterreichende bariatrische Operation zur Ergänzung der Malabsorption bei nicht ausreichendem Gewichtsverlust angeschlossen werden. In ersten tierexperimentellen Untersuchungen wurden neue endoskopische Methoden zur Erstellung von gastrointestinalen Anastomosen beschrieben [21,22]. In einer aktuellen Arbeit wird eine Methode beschrieben, bei der durch den Einsatz von Magneten und einem speziellen Stentsystem bei Patienten mit Magenausgangsstenose eine gastrointestinale Anastomose endoskopisch erzeugt wurde [23].…”
Section: Introductionunclassified